Earthquake geology of Kashmir Basin and its implications for future large earthquakes - Shah, Afroz Ahmad (Springer, 2013)
Two major traces of active thrust faults were identified in the Kashmir Basin (KB) using satellite images and by mapping active geomorphic features. The ~N130°E strike of the mapped thrust faults is consistent with the regional ~NE–SW convergence along the Indian–Eurasian collision zone. The ~NE dipping thrust faults have uplifted the young alluvial fan surfaces at the SW side of the KB. This created a major tectono-geomorphic boundary along the entire strike length of the KB that is characterised by (1) a low relief with sediment-filled sluggish streams to the SE and (2) an uplifted region, with actively flowing streams to the SW. The overall tectono-geomorphic expression suggests that recent activity along these faults has tilted the entire Kashmir valley towards NE. Further, the Mw 7.6 earthquake, which struck Northern Pakistan and Kashmir on 8 October 2005, also suggests a similar strike and NE dipping fault plane, which could indicate that the KB fault is continuous over a distance of ~210 km and connects on the west with the Balakot Bagh fault. However, the geomorphic and the structural evidences of such a structure are not very apparent on the north-west, which thus suggest that it is not a contiguous structure with the Balakot Bagh fault.Therefore, it is more likely that the KB fault is an independent thrust, a possible ramp on the Main Himalayan Thrust, which has uplifting the SW portion of the KB and drowning everything to the NE (e.g. Madden et al. 2011). Furthermore, it seems very likely that the KB fault could be a right stepping segment of the Balakot Bagh fault, similar to Riasi Thrust, as proposed by Thakur et al. (2010). The earthquake magnitude is measured by estimating the fault rupture parameters (e.g. Wells and Coppersmith in Bull Seismol Soc Am 84:974–1002, 1994). Therefore, the total strike length of the mapped KB fault is ~120 km and by assuming a dip of 29° (Avouac et al. in Earth Planet Sci Lett 249:514–528, 2006) and a down-dip limit of 20 km, a Mw of 7.6 is possible on this fault.